VIDEO PRODUCTION AND YOUTH-ADULT COLLABORATION: OPENINGS AND DILEMMAS - Stack, Michelle (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
ABSTRACT. This study explores a collaborative project between high school youth and adult educators (graduate students in education) to create public service announcements. How do young people and educators talk about media, politics, power, and social change? Based on my observations of participant interaction, I argue that power is not dichotomous, with adults necessarily exerting power over youth. The very act of creating a collaborative video can provide a meaningful pedagogical tool to mobilize the individuals involved to engage in conversations about the meaning of social justice and strategies for achieving greater social justice. LA PRODUCTION DE VIDÉOS ET LA COLLABORATION ENTRE LES JEUNES ET LEURS ÉDUCATEURS : DÉBOUCHÉS ET DILEMMES RÉSUMÉ. Cette étude fait l’examen d’un projet collaboratif mené entre des jeunes du secondaire et leurs éducateurs adultes (étudiants à la maîtrise en éducation) pour créer des De quelle manière les jeunes et les éducateurs abordent les média, la politique, le pouvoir et les changements sociaux? Basée sur mes observations des interactions des participants, j’affirme que le pouvoir n’est pas dichotomique, les adultes exerçant leur pouvoir sur les jeunes. L’exercice de créer un vidéo collaboratif offre des outils pédagogiques signifiants. Il permet de mobiliser les individus en les engageant dans des conversations sur le sens de la justice sociale et les stratégies possibles pour augmenter sa prévalence.